What the Taylor Rule Predicts for the Case of Turkiye - Osman Cenk Kanca (Maliye Çalışmaları Dergisi)
The Taylor rule is a simple monetary policy that suggests how central banks can mechanically arrange their interest policies in accordance with inflation-output deficit. This study aims to test the Taylor rule on the Turkish economy in particular. In this context, the study uses quarterly data from 2003 Q1-2019 Q4 for the Turkish economy along side certain vector autoregression (VAR) models as a time series method. As a result of the performed analyses, the interest rates in Turkiye were determined to not occur in accordance with the Taylor rule. This empirical result does not conform with the basic objective of the Turkish Central Bank, whose goal was to maintain price stability for this period. Thus, the Central Bank, being responsible of monetary policies, can be said to need to pay attention to the movements of inflation when establishing interest policies.